Impact of ambient temperature, diurnal temperature range on hyperventilation syndrome emergency admission: a time-series analysis in Beijing, China - Xuan Liu; Qi Zhao; Changping Li; Yuming Guo; Xuan Li; Zhuang Cui; Wenyi Zhang; Jianping Wang; Yongming Zhang; Jinhua Zhao; Ying Ni (BMJ Open)
Objectives To assess the association between ambient temperature and diurnal temperature range (DTR) on emergency admissions for hyperventilation syndrome (HVS).Design Distributed lag non-linear model design was used with a lag time to 5 days.Setting Emergency admission data used were from the Beijing Red Cross Emergency Centre (2017–2018).Participants and exposure Cases were those with emergency visits to the Beijing Emergency Center during the period 2017–2018 and who were given the primary outcome indicator defined as HVS according to the International Classification of Diseases, 10th edition code F45.303. Ambient temperature and DTR were used as exposure factors with adjustments for relative humidity, wind speed, precipitation, seasonality long-term trend and day of the week.Main outcome measure We used the minimum emergency visits temperature as a reference to indicate the relative risk with 95% CI of exposure–response for the risk of HVS visits at different temperatures.Results A u-shape was described between ambient temperature and HVS visits, with a minimum risk at 12°C. Moderate heat (23°C) at lag (0–3) days, extreme heat at lag 0 days, had greatest relative risks on HVS visits, with 2.021 (95% CI 1.101 to 3.71) and 1.995 (95% CI 1.016 to 3.915), respectively. A stronger association between HVS visits and temperature was found in women and aged ≤44 years. Notably, the relationship between DTR and HVS visits appeared a reverse u-shaped. Low DTR (4°C) effect appeared at lag (0–1) days with 0.589 (95% CI 0.395 to 0.878), lasting until lag (0–3) days with 0.535 (95% CI 0.319 to 0.897) and was associated with a reduced risk of HVS visits in women and those aged ≤44 years.Conclusions Ambient temperature and DTR were associated with HVS visits, appearing a differentiation in gender and age groups. Timely prevention strategies during high temperatures and control mild changes in temperature might reduce the risk of HVS.